Outcomes in Third and Fourth Kidney Transplants Based on the Type of Donor. Issue 7 (July 2019) - Dabare, Dilan; Kassimatis, Theodoros; Hodson, James; Khurram, Muhammad Arslan; Papadakis, Georgios; Rompianesi, Gianluca; Shaw, Olivia; Karydis, Nikolaos; Callaghan, Chris; Olsburgh, Jonathon; Mamode, Nizam; Kessaris, Nicos; et al.
Abstract : Background: An increasing number of patients are requiring multiple retransplants. We assessed outcomes of third and fourth kidney transplants, to aid decision making on the most suitable donor type. Methods: Data were collected retrospectively for 2561 transplants, including 69 third and 8 fourth, performed from 2000 to 2017. Demographics and outcomes for the combined third/fourth group were compared to first and second transplants. Within the third/fourth kidney transplant group, comparisons were made between deceased donors (n = 39), live donor HLA-compatible (n = 23) and -incompatible (n = 13) transplants, as well as between standard (n = 25) and extended-criteria (n = 14) deceased donor transplants. Results: Patient survival did not differ significantly by transplant number ( P = 0.532), whereas death-censored graft survival declined progressively, from 89% at 5 years in first, 85% in second and 74% in the third/fourth transplant group ( P < 0.001). Within the combined third/fourth transplant subgroup, 5-year graft survival was found to be 100% in recipients of HLA-compatible live donors, compared to 75% in deceased donors and 53% in HLA-incompatible live donors, although this difference did not reach statistical significance ( P = 0.083). No significant difference in patient survival ( P = 0.356) or complication rates ( P = 0.757) were detected between these groups. For recipients of deceased donors in the third/fourth transplant group, there were no significant differences between standard versus extended-criteria donors for any of the outcomes considered. Conclusions: Despite variable functional outcomes, third and fourth kidney transplant recipients experience comparable patient survival rates to first and second transplants, regardless of the donor type. In selected patients, HLA-incompatible live donors and extended-criteria deceased donors should be considered.